On the moduli of hypersurfaces in toric orbifolds - Bunnett, Dominic (Proceedings of the Edinburgh Mathematical Society, 2024)
We construct and study the moduli of stable hypersurfaces in toric orbifolds. Let X be a projective toric orbifold and $α \in \operatorname{Cl}(X)$ an ample class. The moduli space is constructed as a quotient of the linear system $|α|$ by $G = \operatorname{Aut}(X)$. Since the group G is non-reductive in general, we use new techniques of non-reductive geometric invariant theory. Using the A-discriminant of Gelfand, Kapranov and Zelevinsky, we prove semistability for quasismooth hypersurfaces of toric orbifolds. Further, we prove the existence of a quasi-projective moduli space of quasismooth hypersurfaces in a weighted projective space when the weighted projective space satisfies a certain condition. We also discuss how to proceed when this condition is not satisfied. We prove that the automorphism group of a quasismooth hypersurface of weighted projective space is finite excluding some low degrees.